"A borderline issue": Are there child soldiers in the United States?. Issue 3 (27th May 2018) - Harding, Scott; Kershner, Seth
ABSTRACT: The human rights literature on child soldiers has long emphasized conflict zones in the Global South, fostering the stereotype of the gun-toting African child while ignoring militarizing practices in the West. Of note, the existing human rights legal framework fails to address the reality of Western youth exposed to military recruiting in their schools. Seeking to address this limitation, we examine some of the primary methods the US military employs to "penetrate" American high schools in search of new recruits. We discuss the apparent targeting by military recruiters of communities with large numbers of low-income students, immigrants, and youth of color. Indeed, in many educational settings, students with limited access to college preparatory programs find themselves ensnared in a "web of militarism" that sharply limits their career options. Drawing on primary source material and military recruiting documents, we demonstrate how US schools are sites for the socialization of youth to a culture of militarism and, ultimately, the production of child soldiers. Thus, we argue that the military presence in US schools be included in the debate over the militarization of youth. We conclude by assessing the discourses and organizing strategies employed by US "counter-recruitment" activists, including some of those who use human rights-based arguments to curb militarism in American schools.